Austenitic stainless steel sheet and method for producing same
Ultrafine-grained 300 series stainless steel with controlled alloy compositions and manufacturing processes addresses the low yield strength issue of austenitic stainless steels, achieving high strength, ductility, and corrosion resistance.
Patent Information
- Application Number
- JP2023512141
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-03
- Filing Date
- 2021-08-26
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-08-26
AI Technical Summary
Austenitic stainless steels, such as the 304 and 301 series, have low yield strength, limiting their structural applications, and methods to increase strength, like temper rolling, compromise elongation rates and increase costs.
Development of ultrafine-grained 300 series stainless steel with specific alloy compositions and manufacturing processes, including hot-rolling, cold-rolling, and annealing, to achieve high yield strength and excellent elongation.
The solution provides stainless steel with high strength and ductility, while reducing the use of expensive alloying elements like Ni and Cr, and ensuring excellent corrosion resistance.
Smart Images

Figure 0007603147000003 
Figure 0007603147000004 
Figure 0007603147000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel and a manufacturing method thereof, and more particularly to an austenitic stainless steel that can be used as a variety of materials such as for automobile exterior panels and building components, and a manufacturing method thereof. [Background technology]
[0002] Austenitic stainless steels have excellent formability, work hardening ability, and weldability, and are used in a variety of applications such as transportation parts and construction parts. However, typical general-purpose austenitic stainless steels such as 304 stainless steel and 301 stainless steel have low strength, with a yield strength of 200 to 350 MPa, limiting their application to structures.
[0003] As a method for increasing the yield strength of austenitic stainless steel, temper rolling may be additionally performed, but this method has problems in that the cost increases due to the additional process and the elongation rate of the material is extremely deteriorated.
[0004] Patent Document 1 discloses a method for manufacturing 300 series stainless steel that has small warpage even after half etching by performing two SR (Stress Relief) heat treatments after temper rolling of cold-rolled annealed material for use as a laser metal mask for photoetching. However, Patent Document 1 relates to a manufacturing technology for controlling the etchability and warpage after etching, and the austenitic stability parameter (ASP) value of the austenitic phase is 30 to 50, so there is a risk that the transformation of deformed organic martensite occurs rapidly during forming, resulting in a decrease in elongation.
[0005] Patent Document 2 relates to nuclear power components, and in order to manufacture austenitic stainless steel with an average grain size of 10 μm or less, a long-term heat treatment is performed at 600 to 700°C for 48 hours or more. Since Patent Document 2 requires a long-term heat treatment, there are problems in that productivity decreases and manufacturing costs increase when it is implemented on an actual production line. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2016 / 043125 [Patent Document 2] JP 2020-50940 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an ultrafine-grained 300 series stainless steel which simultaneously satisfies both high yield strength and excellent elongation. [Means for solving the problem]
[0008] The austenitic stainless steel of the present invention contains, by weight, C: 0.005-0.03%, Si: 0.1-1%, Mn: 0.1-2%, Ni: 6-9%, Cr: 16-19%, N: 0.2% or less, with the remainder being Fe and unavoidable impurities. When the thickness of the entire steel material is t, the thickness is 1 / 4t to 3 / 4t. of The average crystal grain size d value is 5 μm or less, the ASP value expressed by the following formula (1) is 10 to 25, the value of the following formula (2) is 435 or more, and the value of the following formula (3) is 6000 or more. (1)551-462*([C]+[N])-9.2*[Si]-8.1*[Mn]-13.7*[Cr]-29*([Ni]+[Cu])-18.5*[Mo]-68*([Nb]+[V]) (2)(1600*[N])+(700 / √d)+(4*ASP)-(20*[Ni])+100 (3) YS*EL-500*([Ni]+[Cr]) In the above formulas (1), (2), and (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], [Mo], [Nb], and [V] represent the weight percentage of each element, YS represents the yield strength (MPa), and EL represents the elongation rate (%).
[0009] Furthermore, in each austenitic stainless steel according to the present invention, the value of the following formula (4) may be 200 or more. (4)Hv-([Ni]+[Cr]) In the formula (4), Hv represents Vickers hardness (Hv), and [Ni] and [Cr] represent the weight percentages of each element.
[0010] In addition, each austenitic stainless steel according to the present invention may further contain, by weight percent, one or more of Cu: 0.4% or less, Mo: 0.2% or less, Nb: 0.25% or less, and V: 0.25% or less.
[0011] In each austenitic stainless steel according to the present invention, the t may be 0.4 to 2.0 mm.
[0012] In addition, each austenitic stainless steel according to the present invention was immersed in a 3.5% NaCl solution at 30°C and measured. pitting corrosion The potential value may be 250 mV or more.
[0013] The method for producing an austenitic stainless steel of the present invention includes the steps of hot rolling a slab containing, by weight, 0.005-0.03% C, 0.1-1% Si, 0.1-2% Mn, 6-9% Ni, 16-19% Cr, 0.2% or less N, with the remainder being Fe and unavoidable impurities, followed by cold rolling at room temperature with a reduction rate of 40% or more, and annealing at 700-850°C.
[0014] Moreover, the method for producing each austenitic stainless steel according to the present invention can be characterized in that after hot rolling, the steel is cold rolled without annealing.
[0015] In addition, the method for producing each austenitic stainless steel according to the present invention may further include a step of temper rolling at a reduction rate of 60% or more. Effect of the Invention
[0016] According to the present invention, it is possible to provide an ultrafine-grained 300 series stainless steel that simultaneously satisfies high strength and high ductility. Furthermore, the present invention provides an austenitic stainless steel that simultaneously satisfies high strength and high ductility, and is economical because it contains less of the expensive alloying elements Ni and Cr. Furthermore, the present invention can provide an austenitic stainless steel that simultaneously satisfies the requirements for high strength and high ductility and can ensure excellent corrosion resistance. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a diagram showing ranges of examples and comparative examples according to values of formula (2) and formula (3). [Figure 2(a)] FIG. 2 is a diagram for comparing the average crystal grain size d between the invention examples and the comparative examples. [Figure 2(b)] FIG. 2 is a diagram for comparing the average crystal grain size d between the invention examples and the comparative examples. [Figure 2(c)] FIG. 2 is a diagram for comparing the average crystal grain size d between the invention examples and the comparative examples. [Diagram 3] Graphs (a) to (c) show strain (%)-stress (MPa) curves for examples of the present invention. [Figure 4] Graphs (a) to (c) show strain (%)-stress (MPa) curves for the comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The austenitic stainless steel of the present invention contains, by weight, C: 0.005-0.03%, Si: 0.1-1%, Mn: 0.1-2%, Ni: 6-9%, Cr: 16-19%, N: 0.2% or less, with the remainder being Fe and unavoidable impurities. When the thickness of the entire steel material is t, the thickness is 1 / 4t to 3 / 4t. of The average crystal grain size d value is 5 μm or less, the ASP value expressed by the following formula (1) is 10 to 25, the value of the following formula (2) is 435 or more, and the value of the following formula (3) is 6000 or more. (1)551-462*([C]+[N])-9.2*[Si]-8.1*[Mn]-13.7*[Cr]-29*([Ni]+[Cu])-18.5*[Mo]-68*([Nb]+[V]) (2)(1600*[N])+(700 / √d )+(4*ASP)-(20*[Ni])+100 (3) YS*EL-500*([Ni]+[Cr]) In the above formulas (1), (2), and (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], [Mo], [Nb], and [V] represent the weight percentage of each element, YS represents the yield strength (MPa), and EL represents the elongation rate (%).
[0019] In the following, preferred embodiments of the present invention will be described. However, the embodiments of the present invention may be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. The terms used in this application are only used to describe specific examples. For example, singular expressions include plural expressions unless the context clearly requires the singular. In addition, it should be noted that the terms "comprise" or "comprise" used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the presence of other features, steps, functions, components, or combinations thereof.
[0020] Meanwhile, unless otherwise defined, all terms used herein should be considered to have the same meaning as that commonly understood by a person having ordinary skill in the art to which the present invention belongs. Therefore, unless clearly defined herein, specific terms should not be interpreted as having an overly ideal or formal meaning. For example, in this specification, singular expressions include plural expressions unless there is a clear exception in the context. In addition, in this specification, the terms "about," "substantially," and the like are used in the sense of a numerical value or close to a numerical value when the tolerances of manufacturing and materials inherent in the referred meaning are presented, and are used to prevent unconscionable infringers from unfairly exploiting the disclosure in which precise or absolute numerical values are referred to in order to aid in the understanding of the present invention.
[0021] Austenitic stainless steel is used in various applications due to its excellent formability, work hardening ability, and weldability, but it has a drawback of low yield strength, and when temper rolling is performed to increase the yield strength, there is a problem that the elongation rate is inferior. The inventors of the present invention have focused on ultrafine-grained austenitic stainless steel as a steel material that simultaneously satisfies high yield strength and excellent elongation rate. However, even though it is called ultrafine grained, it does not simultaneously satisfy high yield strength and excellent elongation rate. Since the Ni and Cr contents differ for each steel type, the amount of martensite transformation during cold working differs depending on the stability of the austenite phase, and the tensile curve characteristics differ depending on the TRIP (Transformation Induced Plasticity) transformation behavior, the yield strength and elongation rate also differ greatly for each steel even though they are called ultrafine-grained austenitic stainless steel. In consideration of these influences, the inventors of the present invention have come up with an ultrafine-grained austenitic stainless steel that can simultaneously realize high strength and high ductility.
[0022] The austenitic stainless steel of the present invention contains, by weight, 0.005-0.03% C, 0.1-1% Si, 0.1-2% Mn, 6-9% Ni, 16-19% Cr, 0.2% or less N, with the remainder being Fe and unavoidable impurities, and may optionally further contain one or more of 0.4% or less Cu, 0.2% or less Mo, 0.25% or less Nb, and 0.25% or less V.
[0023] The reasons for limiting the alloy composition will be described in detail below. The C (carbon) content is 0.005 to 0.03% by weight. C is an element that stabilizes the austenite phase. In consideration of this, in the present invention, C is added in an amount of 0.005 wt% or more. However, if the C content is excessive, chromium carbide is formed during low-temperature annealing, which causes a problem of reducing intergranular corrosion resistance, so in the present invention, the C content is limited to 0.03 wt% or less. The Si (silicon) content is 0.1 to 1% by weight. Silicon is an element added as a deoxidizer during steelmaking, and when bright annealing is performed, it forms silicon oxide in the passive film, which improves the corrosion resistance of steel. In consideration of this, silicon is added in an amount of 0.1 wt% or more in the present invention. However, since excessive silicon content can cause a problem of reduced ductility, the silicon content is limited to 1.0 wt% or less in the present invention.
[0024] The Mn (manganese) content is 0.1 to 1.0% by weight. Mn is an element that stabilizes the austenite phase. In consideration of this, in the present invention, Mn is added in an amount of 0.1 wt% or more. However, since an excessive Mn content reduces corrosion resistance, in the present invention, the Mn content is limited to 1.0 wt% or less. The Ni (nickel) content is 6.0 to 9.0% by weight. Ni is an element that stabilizes the austenite phase and has the effect of softening the steel material. Taking this into consideration, Ni is added in an amount of 6.0 wt% or more in the present invention. However, since an excessive Ni content increases the cost, the Ni content is limited to 9.0 wt% or less in the present invention.
[0025] The Cr (chromium) content is 16.0 to 19.0% by weight. Cr is a major element for improving the corrosion resistance of stainless steel. In consideration of this, Cr is added in an amount of 16.0 wt% or more in the present invention. However, if the Cr content is too high, the steel material becomes hard and the transformation of deformed organic martensite during cold rolling is inhibited, so the Cr content is limited to 19.0 wt% or less in the present invention. The N (nitrogen) content is 0.2% by weight or less. N is an element that stabilizes the austenite phase and improves the strength of steel. However, if the N content is excessive, the steel becomes hard and the hot workability deteriorates, so in the present invention, the N content is limited to 0.2 wt% or less.
[0026] The reasons for limiting the contents of the optional alloying elements Cu, Mo, Nb, and V will be described in detail below. The Cu content may be less than or equal to 0.4% by weight. Cu is an element that stabilizes the austenite phase. However, if the Cu content is excessive, the corrosion resistance of the steel material decreases and the cost increases, so in the present invention, the Cu content is limited to 0.4 wt% or less. The Mo (molybdenum) content may be 0.2% by weight or less. Mo has the effect of improving corrosion resistance and workability, but if the Mo content is excessive, there is a problem of increased costs, so in the present invention, the Mo content is limited to 0.2 wt% or less. The content of Nb (niobium) or V (vanadium) may be less than or equal to 0.25% by weight. When added, Nb and V form (Nb, V)(C, N) precipitates, which have the effect of suppressing the growth of crystal grains. However, if the content of Nb and V is excessive, there is a problem of increased costs, so in the present invention, the content of Nb and V is limited to 0.25 wt% or less, respectively.
[0027] The remaining component of the present invention is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from raw materials or the surrounding environment, and it is not possible to exclude them. The above impurities are known to anyone skilled in the normal manufacturing process, and therefore, the entire contents of the impurities will not be specifically mentioned in this specification.
[0028] In addition to limiting the content of each alloying element in the stainless steel of the present invention as described above, the stainless steel can be further limited as follows. The ASP (Austenitic Stability Parameter) value expressed by the formula (1) may be 10 to 25 or less. (1)551-462*([C]+[N])-9.2*[Si]-8.1*[Mn]-13.7*[Cr]-29*([Ni]+[Cu])-18.5*[Mo]-68*([Nb]+[V]) In formula (1), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], [Mo], [Nb], and [V] represent the weight percent of each element. For elements that are not added, the weight percent is calculated by substituting 0 weight percent into formula (1). Equation (1) represents the temperature at which 50% of austenite transforms into martensite when stainless steel is deformed with 0.3 true strain, and is used as an index of the stability of the austenite phase. The lower the value of equation (1), the higher the stability of the austenite phase, and the less processed martensite is transformed during deformation. If the value of formula (1) is less than 10, the amount of TRIP transformation from austenite to martensite by cold rolling is low, so the proportion of martensite in the cold rolled material is low and the proportion of retained austenite phase is high. As the amount of processed organic martensite decreases, the proportion of reverted austenite phase by low-temperature annealing decreases, and the proportion of retained austenite phase that does not transform to martensite is high, making it difficult to ensure ultrafine grains. If the value of formula (1) exceeds 25, the TRIP transformation by cold rolling is activated, but there is a problem that the elongation value is low due to an excessively fast TRIP transformation rate.
[0029] The value of formula (2) may be 435 or greater. (2)(1600*[N])+(700 / √d )+(4*ASP)-(20*[Ni])+100 In formula (2), [N] and [Ni] mean the weight percentage of each element. ASP means the ASP value in formula (1). d is the thickness of the entire steel material, from 1 / 4t to 3 / 4t. of It means the average grain size. In the present invention, t may be 0.4 to 2.0 mm. Materials having a thickness of 0.4 to 2.0 mm are often used for structural parts, and according to the present invention, it is possible to provide an austenitic stainless steel having high strength and high ductility within this thickness range. According to one embodiment of the present invention, d may be 5 μm or less. If d exceeds 5 μm, it will have a low yield strength according to the Hall-Petch equation, which will cause the YS*El value to be low. Formula (2) is a parameter for ensuring high strength, taking into consideration the N and Ni contents, grain size, and the stability of the austenite phase, which are factors that affect strength. If the value of formula (2) is less than 435, it is not possible to ensure a sufficiently high strength.
[0030] The value of formula (3) may be 6000 or more. (3) YS*EL-500*([Ni]+[Cr]) In formula (3), YS is the yield strength (MPa), EL is the elongation rate (%), and [Ni] and [Cr] are the weight percentages of each element. The YS*EL value in formula (3) is greatly affected by the Cr and Ni contents. For example, when the Cr and Ni contents are low, TRIP transformation occurs easily, and the YS*EL value tends to be high. If the value of formula (3) is less than 6000, there is a problem that high strength and high ductility cannot be achieved at the same time.
[0031] The value of formula (4) may be 200 or more. (4)Hv-([Ni]+[Cr]) In formula (4), Hv is the Vickers hardness (Hv), and [Ni] and [Cr] are the weight percentages of each element. The Hv value in formula (4) is greatly affected by the Cr and Ni contents. For example, when the Cr and Ni contents are low, TRIP transformation occurs easily, which increases the amount of transformation of work-induced martensite during cold deformation. As a result, the hardness of the steel material increases. If the value of formula (4) is less than 200, there is a problem that sufficient hardness cannot be secured.
[0032] The austenitic stainless steel according to the present invention not only satisfies both high strength and high ductility, but also has excellent corrosion resistance. The austenitic stainless steel according to the present invention was measured by immersing it in a 3.5% NaCl solution at 30°C. pitting corrosion The potential value may be 250 mV or more. The austenitic stainless steel according to one example of the present invention may have a tensile strength of 1750 MPa or more after temper rolling. A method for producing an austenitic stainless steel according to one embodiment of the present invention includes the steps of hot rolling a slab containing, by weight, 0.005-0.03% C, 0.1-1% Si, 0.1-2% Mn, 6-9% Ni, 16-19% Cr, 0.2% or less N, with the remainder being Fe and unavoidable impurities, followed by cold rolling at room temperature with a reduction rate of 40% or more, and annealing at 700-850°C. If the reduction rate during cold rolling is less than 40%, the amount of TRIP transformation in the austenitic stainless steel of the present invention having an ASP range of 10 to 25 is excessively low, so that the martensite fraction of the cold rolled material is low and the fraction of the retained austenite phase is high. As the amount of processed martensite decreases, the proportion of reverse transformed austenite phase by the subsequent low-temperature annealing decreases, and the fraction of the retained austenite phase that does not transform into martensite is high, making it difficult to ensure ultrafine crystal grains.
[0033] According to the present invention, the hot-rolled material can be cold-rolled and then low-temperature annealed at 700 to 850°C. If the low-temperature annealing temperature is less than 700°C, there is a problem that recrystallization from the processed organic martensite phase to the reverse-transformed austenite phase does not occur. On the other hand, if the low-temperature annealing temperature exceeds 850°C, the grain size of the reverse-transformed austenite may become coarse, resulting in a low yield strength. According to one embodiment of the present invention, after hot rolling, the steel sheet can be cold rolled without annealing. In addition, following the above-mentioned manufacturing steps, a step of temper rolling at a rolling reduction of 60% or more may be included in order to further increase strength.
[0034] The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are merely for illustrating and explaining the present invention in more detail, and are not intended to limit the scope of the present invention, since the scope of the present invention is determined by the matters described in the claims and matters reasonably inferred therefrom. <Example> After hot rolling the slab having the composition shown in Table 1, it was not annealed but cold rolled at room temperature with a total rolling reduction of 40% or more, and then annealed at 700 to 850°C to produce cold-rolled annealed materials with thicknesses of 0.4 to 2.0 mm.
[0035] In Table 1, ASP is a value derived by substituting the alloy composition in Table 1 into the following formula (1), which indicates the degree of stabilization of the austenite phase. (1)551-462*([C]+[N])-9.2*[Si]-8.1*[Mn]-13.7*[Cr]-29*([Ni]+[Cu])-18.5*[Mo]-68*([Nb]+[V]) In formula (1), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], [Mo], [Nb], and [V] mean the weight percentage of each element.
[0036] [Table 1]
[0037] In Table 2, d is the thickness between 1 / 4t and 3 / 4t, where t is the total thickness of the cold-rolled annealed material in Table 1. of It means the average crystal grain size (μm). Formula (2) in Table 2 means the value derived by the following formula (2). (2)(1600*[N])+(700 / √d )+(4*ASP)-(20*[Ni])+100 The value of equation (2) was derived by substituting the weight percentages of [N] and [Ni] and the ASP values in Table 1 and the d value in Table 2. Equation (3) in Table 2 means the value derived by the following equation (3). (3) YS*EL-500*([Ni]+[Cr])
[0038] The value of equation (3) was derived by substituting the yield strength (YS, MPa) and elongation (EL, %) measured under the conditions described below and the weight percentages of [Ni] and [Cr] in Table 1. The yield strength (YS, MPa) and elongation (EL, %) were measured after performing a tensile test on the produced cold-rolled annealed material using test pieces according to JIS13B standard at room temperature with a crosshead speed in the range of 10 mm / min to 20 mm / min. Equation (4) in Table 2 means the value derived by the following equation (4). (4)Hv-([Ni]+[Cr]) The value of the formula (4) was derived by substituting the Vickers hardness (Hv) measured under the conditions described below and the weight percentages of [Ni] and [Cr] in Table 1. The Vickers hardness (Hv) is a value measured using a Vickers hardness tester under a load of 2 kgf. Table 2 pitting corrosion The potential (mV) was measured by immersing the cold-rolled annealed material in a 3.5% NaCl solution at 30°C.
[0039] [Table 2]
[0040] As shown in Tables 1 and 2, inventive examples 1 to 8, the ASP value was 10 to 25, the d value was 5 μm or less, the value of formula (2) was 435 or more, and the value of formula (3) was 6000 or more, and high strength, high ductility, and excellent corrosion resistance were ensured. In addition, as shown in Table 2, the value of formula (4) of invention examples 1 to 8 was 200 or more, pitting corrosion The potential was 250 mV or more. Comparative Examples 6 to 18 were outside the ASP value range limited by the present invention. Comparative Examples 6 to 13 and 18, which had an ASP value exceeding 25, showed low elongation rates due to excessively fast TRIP transformation rates during forming. Comparative Examples 14 to 17, which had an ASP value of less than 10, were unable to secure ultrafine grains due to a high fraction of retained austenite phase. In Comparative Examples 1 to 5, 7, 10, and 13 to 17, the crystal grains were formed coarsely, beyond the range of the d value limited by the present invention, and as a result, high strength and high ductility were not simultaneously satisfied. Comparative Examples 3 to 5 and 13 to 17 did not satisfy the range of values of formula (2) defined by the present invention, and as a result, did not simultaneously satisfy high strength and high ductility. Comparative Examples 2 and 5 to 17 did not satisfy the range of values of formula (3) defined by the present invention, and as a result, did not simultaneously satisfy high strength and high ductility. Comparative Examples 1, 3 to 5, 7, 10, 12, and 14 to 17 did not satisfy the range of values of formula (4) defined by the present invention, and as a result, did not ensure sufficient hardness. Comparative Example 18 contains a large amount of Mn, so the corrosion resistance is reduced. pitting corrosion The potential was low at 30 mV.
[0041] Fig. 1 is a diagram showing the ranges of the examples and comparative examples according to the values of formula (2) and formula (3). Referring to Fig. 1, it can be seen that all the examples of the invention are included within the ranges of the values of formula (2) and formula (3) defined by the present invention, and it is possible to provide an austenitic stainless steel that simultaneously satisfies high strength and high ductility properties within the ranges. On the other hand, the comparative examples do not satisfy the range of the value of formula (2) and / or the range of the value of formula (3), and in this case, it is difficult to simultaneously satisfy high strength and high ductility properties. Figures 2(a) to 2(c) are diagrams for comparing the average crystal grain size d between the invention examples and the comparative examples. Figures 2(a) and 2(b) are diagrams according to the present invention, and Figure 2(c) is a diagram according to the comparative example. Comparing Figures 2(a), 2(b) and 2(c), it can be seen that the austenitic stainless steel according to the present invention has ultrafine grains with a d value of 5 μm or less. FIGS. 3(a) to 3(c) are graphs showing the Strain (%)-Stress (MPa) curves of the examples of the invention. FIG. 4(a) to FIG. 4(c) show strain (%)-stress (MPa) curves of the comparative example.
[0042] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and it should be understood that various changes and modifications can be made by those skilled in the art without departing from the concept and scope of the following claims. [Industrial Applicability]
[0043] The austenitic stainless steel according to the present invention simultaneously satisfies high strength and high ductility, is economical by reducing the content of expensive alloy elements Ni and Cr, and ensures excellent corrosion resistance. Therefore, it can be used as a variety of materials for automobile exterior panels, building parts, etc.
Claims
1. The alloy contains, by weight, C: 0.005-0.03%, Si: 0.1-1%, Mn: 0.1-2%, Ni: 6-9%, Cr: 16-19%, N: 0.2% or less, and the remainder being Fe and unavoidable impurities; An austenitic stainless steel sheet characterized in that, when the thickness of the entire steel material is t, the average crystal grain size d value at thicknesses 1 / 4t to 3 / 4t is 5 μm or less, the ASP value expressed by formula (1) is 10 to 25, the value of formula (2) is 435 or more, and the value of formula (3) is 6000 or more. (1) 551-462*([C]+[N])-9.2*[Si]-8.1*[Mn]-13.7*[Cr]-29*([Ni]+[Cu])-18.5*[Mo]-68*([Nb]+[V]) (2) (1600*[N])+(700 / √d)+(4*ASP)-(20*[Ni])+100 (3) YS*EL-500* ([Ni]+[Cr]) (In the formulas (1), (2), and (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], [Mo], [Nb], and [V] represent the weight percentage of each element, YS represents the yield strength (MPa), and EL represents the elongation rate (%).)
2. 2. The austenitic stainless steel sheet according to claim 1, characterized in that the value of formula (4) is 200 or more. (4) Hv-([Ni]+[Cr]) (In formula (4), Hv is the Vickers hardness (Hv), [Ni] and [Cr] are the weight percentages of each element.)
3. 2. The austenitic stainless steel sheet according to claim 1, further comprising, by weight percent, one or more of Cu: 0.4% or less, Mo: 0.2% or less, Nb: 0.25% or less, and V: 0.25% or less.
4. 2. The austenitic stainless steel sheet according to claim 1, wherein t is 0.4 to 2.0 mm.
5. 2. The austenitic stainless steel sheet according to claim 1, characterized in that the pitting potential value measured by immersion in a 3.5% NaCl solution at 30° C. is 250 mV or more.
6. A method for producing an austenitic stainless steel sheet according to claim 1, A step of hot rolling a slab containing, by weight, C: 0.005-0.03%, Si: 0.1-1%, Mn: 0.1-2%, Ni: 6-9%, Cr: 16-19%, N: 0.2% or less, and the remainder being Fe and unavoidable impurities, and then cold rolling the slab at room temperature with a rolling reduction of 40% or more; A method for producing an austenitic stainless steel sheet, comprising the step of annealing at 700 to 850°C.
7. The method for producing an austenitic stainless steel sheet according to claim 6, characterized in that after the hot rolling, the sheet is cold rolled without being annealed.
8. The method for producing an austenitic stainless steel sheet according to claim 6, further comprising the step of temper rolling at a rolling reduction of 60% or more.
Citation Information
Patent Citations
JP1975056985A
Power supply controller
JP1983043019A
Adhesive acid curing resin protective coating for concrete and steel
JP1984039370A
Stainless steel for engine gasket excellent in formability and its manufacture
JP1992214841A
High strength stainless steel and its production
JP1993039549A
